Assasement and Experimental Procedure Polycystic Ovary Syndrome Rat Model: Review - Kurniawati, Erna Yovi; Pramono, Noor; Hidayat, Syarief Thaufik; Mahati, Endang (Universitas Bengkulu, 2023)
A complicated endocrine condition that affects many women worldwide is called polycystic ovarian syndrome, or PCOS. The use of rat models has greatly aided research on many facets of PCOS. In addition to discussing the parameters, evaluation techniques, and indicators pertinent to PCOS research, this study evaluates the standard circumstances of PCOS rat models. Our knowledge of PCOS has improved due to investigating endocrine, hormonal, inflammatory, oxidative stress, metabolic, genetic, and microbiota-related factors in these models. The results highlight how important it is to use PCOS rat models to understand the complexities of this illness and offer possible treatment avenues.